Prescription for the People An Activist's Guide to Making Medicine Affordable for All - Quigley, Fran (Cornell University Press, 2017)
In Prescription for the People, Fran Quigley diagnoses our inability to get medicines to the people who need them and then prescribes the cure. He delivers a clear and convincing argument for a complete shift in the global and U.S. approach to developing and providing essential medicines-and a primer on how to make that change happen. Globally, 10 million people die each year because they are unable to pay for medicines that would save them. The cost of prescription drugs is bankrupting families and putting a strain on state and federal budgets. Patients' desperate need for affordable medicines clashes with the core business model of the powerful pharmaceutical industry, which maximizes profits whenever possible. It doesn't have to be this way. Patients and activists are aiming to make all essential medicines affordable by reclaiming medicines as a public good and a human right, instead of a profit-making commodity. In this book, Quigley demystifies statistics and terminology, offers solutions to the problems that block universal access to medicines, and provides a road map for activists wanting to make those solutions a reality.